THIS CHOCOLATE IS NO MORE SWEET - Ravi Kumar, Pyla (International Journal of Psychosocial Rehabilitation, 2020)
Child sexual abuse in India is a serious problem. Though not unique to India, the country does have characteristics that add to the complexity and severity of the problem. A problem that is only beginning to come into light in India, rape, sexual abuse, and sexual harassment are worldwide issues of gender violence. Bitter Chocolate is a book that deals with child sexual abuse in India. Pinki Virani’s work seamlessly blending her journalistic and writing skills places her among the few international authors whose writing results in rendering direct service towards Indian citizens, sometimes one at a time.